PENENTUAN CERITA EBHI DAN KHANDEI SEBAGAI BAHAN BACAAN ANAK - Muntihanah, Muntihanah (METASASTRA: Jurnal Penelitian Sastra, 2016)
Jayapura has many variaties of folklore. Unfortunately, this potential has not been used optimally as a reference of children reading for basic school.   This paper aims to know the chance of the ‘Ebhi dan Khandei’ story to be a source of children reading reference based on three criteria, namely the simplicity of structure; the character value; and the correlation between the structure of story and the developmental of child intelligence. Data analysis uses theory of structural; theory of developmental intelligence; and character value. It is concluded that ‘Ebhi and Khandei is recommended to be a source of reading for the children under the age of 7-11 years old because the story has a simple structure. The simplicity of structure reflected on the linear plot, the flat character, the concrete setting, the limited conflict, the stile on lexical element uses base world, and element of grammatical uses declarative sentence. Besides those components, this story also contains of good character value. Those characters are honesty and obey to the social rules.